Efficacy of antiviral therapy and host–virus interactions visualised using serial liver sampling with fine-needle aspirates - Samuel C. Kim; Jeffrey J. Wallin; Yanal Ghosheh; Muhammad Atif Zahoor; Juan Diego Sanchez Vasquez; Shirin Nkongolo; Scott Fung; Patricia Mendez; Jordan J. Feld; Harry L.A. Janssen; Adam J. Gehring (JHEP Reports, 2023)
Background & Aims: Novel therapies for chronic hepatitis B (CHB), such as RNA interference, target all viral RNAs for degradation, whereas nucleoside analogues are thought to block reverse transcription with minimal impact on viral transcripts. However, limitations in technology and sampling frequency have been obstacles to measuring actual changes in HBV transcription in the liver of patients starting therapy. Methods: We used elective liver sampling with fine-needle aspirates (FNAs) to investigate the impact of treatment on viral replication in patients with CHB. Liver FNAs were collected from patients with CHB at baseline and 12 and 24 weeks after starting tenofovir alafenamide treatment. Liver FNAs were subjected to single-cell RNA sequencing and analysed using the Viral-Track method. Results: HBV was the only viral genome detected and was enriched within hepatocytes. The 5′ sequencing technology identified protein-specific HBV transcripts and showed that tenofovir alafenamide therapy specifically reduced pre-genomic RNA transcripts with little impact on HBsAg or HBx transcripts. Infected hepatocytes displayed unique gene signatures associated with an immunological response to viral infection. Conclusions: Longitudinal liver sampling, combined with single-cell RNA sequencing, captured the dynamic impact of antiviral therapy on the replication status of HBV and revealed host–pathogen interactions at the transcriptional level in infected hepatocytes. This sequencing-based approach is applicable to early-stage clinical studies, enabling mechanistic studies of immunopathology and the effect of novel therapeutic interventions. Impact and Implications: Infection-dependent transcriptional changes and the impact of antiviral therapy on viral replication can be measured in longitudinal human liver biopsies using single-cell RNA sequencing data.